Jane Austen's Sense & Sensibility - Thompson, Emma (London Bloomsbury, 1995)
This is the story of Elinor and Marianne Dashwood, two strikingly different sisters. Forced to move to a cottage in Devonshire after their father's death, the sisters both fall in love with men whom they discover are not what they seem.
Include Illustrations
Keywords: Sense and sensibility (Motion picture : 1995)